(untitled) (ACME, 2025)
Fondo Patturelli places the city of Capua among those sanctuary complexes in which the enormous quantity of votive heritage collected, over ten thousand pieces, allows us to know and reconstruct, not without difficulty, the religious and votive panorama of this sacred area closely connected to the religious, social and territorial life of the Campania community. The god Eros appears inside the repertoire of exceptional numerical consistency and typological variety of the multiple representations of divinities that over time flank the maternal and curotrophic goddess of the archaic age. Apparently, Eros plays a secondary role, widespread between the 3rd and 2nd centuries BC, but the quantity of attestations bringing a considerable number of testimonies, even outside the Campania region, requires a specific study of this god with the purpose of delineating his figure in the most complete way. The general context, also in relation to other clay categories present in the Fondo Patturelli, suggests its specific vocation and seems to confirm its role as intimately connected to the biological and social protection of the community, especially women, to guarantee a fundamental continuity.